Awareness and Uptake of Family Screening in Patients Diagnosed with Colorectal Cancer at a Young Age - Niamh M. Hogan; Marion Hanley; Aisling M. Hogan; Margaret Sheehan; Oliver J. McAnena; Mark P. Regan; Michael J. Kerin; Myles R. Joyce (Gastroenterology Research and Practice)
Background. One-fifth of people who develop colorectal cancer (CRC) have a first-degree relative (FDR) also affected. There is a large disparity in guidelines for screening of relatives of patients with CRC. Herein we address awareness and uptake of family screening amongst patients diagnosed with CRC under age 60 and compare guidelines for screening. Study Design. Patients under age 60 who received surgical management for CRC between June 2009 and May 2012 were identified using pathology records and theatre logbooks. A telephone questionnaire was carried out to investigate family history and screening uptake among FDRs. Results. Of 317 patients surgically managed for CRC over the study period, 65 were under age 60 at diagnosis (8 deceased). The mean age was 51 (30–59). 66% had node positive disease. 25% had a family history of colorectal cancer in a FDR. While American and Canadian guidelines identified 100% of these patients as requiring screening, British guidelines advocated screening for only 40%. Of 324 FDRs, only 40.9% had been screened as a result of patient’s diagnosis. Conclusions. Uptake of screening in FDRs of young patients with CRC is low. Increased education and uniformity of guidelines may improve screening uptake in this high-risk population.